Layered Rare-Earth Hydroxide Unilameller Nanosheets: Synthesis, Characterization, and Adsorption - Solomon Omwoma; Adongo Stephen Odongo; Zablon Otieno; Silas Lagat; Joseph Owuor Lalah (Journal of Chemistry)
Unilameller nanosheets with a lateral dimension of one nanometer have been isolated from a colloidal solution of europium-containing layered rare-earth hydroxide (LRH) material by the flocculation method. The nanosheets were achieved by changing pH of the colloidal solution from 6.7 to 11.5. The resultant flocculated nanosheets show high efficiency in sorption of fluoride anions from aqueous media (40 mmol/g), providing a potentially useful sorbent material for water purification technology. The sorbent material is demonstrated to be reusable for at least ten times without a significant loss of adsorption efficiency. And the results fit the Langmuir adsorption curve, indicating the chemisorption nature of the nanosheets. Most importantly, the isolated nanosheets are expected to widen the applicability and flexibility in material synthesis using two-dimensional nanomaterials.